MOTIVASI INDONESIA MENJALIN KERJASAMA BIDANG KEDIRGANTARAAN DENGAN TIONGKOK - Vidianty, Rini; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research explains Indonesian’s motive established aerospace cooperation with China. Indonesia and China signed a cooperation agreement on Exploration and Utilization of Space for Peaceful Purposes on 2 October 2013. The areas of this cooperation include the field of launching space satellites, earth observation, satellite communications, satellite navigation, telemitri, tracking and control, rocket probe, facility space, material satellites, space science, training or education, and aeronautics technology.This research used qualitative methods which is done by explaining the case based on existing facts. The techniques used to collects data to study the case is library research in the form of journals, books, thesis, reports, working papers, magazine, and website to explain Indonesian’s motive established space cooperation with China. The theoretical framework applied in this research are realism perspective, security theory of Barry Buzan and national interests concept from Hans J. Morgenthau.This study shows that Indonesia is the motivation for the national interests and seeks to improve the capacity of leading space faring nation. This partnership is a step to improve the capacity of Indonesia.Keywords: cooperation, national interest, Indonesia, Tiongkok, aerospace